2003
DOI: 10.1111/j.1460-9568.2003.02995.x
|View full text |Cite
|
Sign up to set email alerts
|

Pain processing within the primary somatosensory cortex in humans

Abstract: To investigate the processing of noxious stimuli within the primary somatosensory cortex (SI), we recorded magnetoencephalography following noxious epidermal electrical stimulation (ES) and innocuous transcutaneous electrical stimulation (TS) applied to the dorsum of the left hand. TS activated two sources sequentially within SI: one in the posterior bank of the central sulcus and another in the crown of the postcentral gyrus, corresponding to Brodmann's areas 3b and 1, respectively. Activities from area 3b co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 43 publications
(80 reference statements)
7
45
0
Order By: Relevance
“…We did not test whether the response showed adaptation or not. Unexpectedly, noxious pinch stimulation near a whisker did not produce any significant response in all neurons tested, in spite of the evidence that the primary sensory cortex responds to noxious stimuli revealed by imaging methods such as MEG, PET or fMRI (Inui, 2003). This discrepancy might be accounted for as follows: First, our patch-clamp recordings were made under anesthesia that presumably depressed nociceptive responses.…”
Section: Synaptic Responses Of Neurons In Sensory Cortexmentioning
confidence: 79%
“…We did not test whether the response showed adaptation or not. Unexpectedly, noxious pinch stimulation near a whisker did not produce any significant response in all neurons tested, in spite of the evidence that the primary sensory cortex responds to noxious stimuli revealed by imaging methods such as MEG, PET or fMRI (Inui, 2003). This discrepancy might be accounted for as follows: First, our patch-clamp recordings were made under anesthesia that presumably depressed nociceptive responses.…”
Section: Synaptic Responses Of Neurons In Sensory Cortexmentioning
confidence: 79%
“…Although much attention has been given to sensorimotor interaction in SI, there is little evidence of such a phenomenon in the SII and the role of SII in motor execution has not been fully elucidated in humans. Compared with the SI, the SII is speculated to serve a higher level of cognitive function in somatosensory information processing, such as attention, decision-making, object recognition, and the integration of nociceptive and non-nociceptive inputs [60][61][62][63][64] . Our results show that these cortical areas play different roles in the function of sensorimotor integration.…”
Section: Implications From Imaging Studiesmentioning
confidence: 99%
“…A magnetoencephalographic study found that innocuous cold uniquely activates the posterior insular cortex, while noxious cold also excites SII [6]. Painful electrical stimulation of the first division of the trigeminal nerve in humans activates the SII but not the SI cortex [21]. The parietal operculum (SII) rather than the anterior insula was found to be involved with raised heat pain thresholds in 6 stroke patients with involvement of SII and/or anterior insula [22], while a patient with a tumour involving the parietal operculum and posterior insula (subsequently removed) had interference with both mechanical and thermal pain sensations [23].…”
Section: Discussionmentioning
confidence: 99%